Thực hiện phép tính: a, (x+3)(x-3)-(x-2)(x+5) b, (2x^3-11x^2+6x-5):(2x^2-x+1) c, (x+1)(x^2-x+1)-(3+x)(9-3x+x^2) d, (2x+3)(4x^2-6x+9)-2(4x^3-1)

Question

Thực hiện phép tính: a, (x+3)(x-3)-(x-2)(x+5) b, (2x^3-11x^2+6x-5):(2x^2-x+1) c, (x+1)(x^2-x+1)-(3+x)(9-3x+x^2) d, (2x+3)(4x^2-6x+9)-2(4x^3-1) e, (x^3-3x^2+3xy^2-y^3):(x^2-2xy+y^2)

in progress 0
Kaylee 9 phút 2021-09-15T02:32:55+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-15T02:33:56+00:00

    a, $(x+3)(x-3)-(x-2)(x+5)$

    $=x^2-9-(x^2+5x-2x-10)$

    $=x^2-9-x^2-3x+10$

    $=1-3x$

    b, $\dfrac{2x^3-11x^2+6x-5}{2x^2-x+1}$

    $=\dfrac{x^3-10x^2-x^2+5x+x-5}{2x^2-x+1}$

    $=\dfrac{x^2(x-5)-x(x-5)+(x-5)}{2x^2-x+1}$

    $=\dfrac{(x-5)(x^2-x+1)}{2x^2-x+1}$

    $=x-5$

    c, $(x+1)(x^2-x+1)-(3+x)(9-3x+x^2)$

    $=x^3+1-(27+x^3)$

    $=x^3+1-27-x^3$

    $=-26$

    d, $(2x+3)(4x^2-6x+9)-2(4x^3-1)$

    $=8x^3+27-8x^3+2$

    $=29$

    e, $\dfrac{x^3-3x^2y+3xy^2-y^3}{x^2-2xy+y^2}$

    $=\dfrac{(x-y)^3}{(x-y)^2}$

    $=x-y$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )